The dynamic impact of FX interventions on financial markets - Malte Rieth; Lukas Menkhoff; Tobias Stöhr (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Evidence on the effectiveness of FX interventions in the prevailing higher frequency approaches leaves a gap at horizons going beyond a few days. This is addressed by identifying a structural vector autoregressive model for the daily frequency with an external instrument. Using Japanese data, we find that FX interventions significantly affect exchange rates, although the effect is smaller than in emerging markets, and this impact persists for up to a year. There is no major effect on interest rates, but stock prices increase in line with currency devaluation, in particular those of large (exporting) firms. The results qualitatively hold for US and UK interventions.
Keywords: F31; F33; E58; 330; Foreign exchange intervention; structural VAR; exchange rates; interest rates; stock prices